Adherence to antidepressant drugs in the primary care setting
Depression is a common affective disorder that affects millions of individuals worldwide, characterized by sadness, hopelessness, and loss of interest in activities in general. Although the precise origins of depression are not entirely understood, a mix of genetic, environmental, and psychological variables are believed to be responsible. Combining therapy, such as cognitive-behavioral therapy, with antidepressants, is the most effective treatment. At least on the first observation, most depressive patients are treated in the primary care context. However, in this context, poor antidepressant adherence has been reported, even when compared with other medications. In the treatment of depression, this reality contributes to worse outcomes, more relapses, higher chronicity, morbidity, and costs. In this review, potentially modifiable factors influencing the adherence to treatment of depression in the primary care setting were identified and discussed. The most frequent reasons found for treatment non-adherence in depressive patients are related to their own lack of scientific knowledge about the disease and antidepressant drugs, namely the presence of false beliefs and social stigma. Therefore, belief-focused interventions, assertive information about depression and antidepressant drugs given during consultation, active involvement of caregivers and family members, incorporating more mental health professionals, such as psychologists, and a fine articulation with mental health services are valuable approaches to overcome this issue. These interventions will provide more quality time in the doctor-patient relationship and higher levels of mental health education in the community. To implement these strategies is mandatory to invest in different resources in the primary care system.